Coba Pembuatan Donat Dengan Subtitusi Tepung Jali Terhadap Tepung Terigu Berprotein Sedang - Salim, Chairul; Sembiring, Vienna Artina; Chandra, Florencia Tania (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
Indonesia is rich in various kinds of cakes and bread. One of them is donut bread. In addition, the author decided to process jali seeds into jali seed flour to be used as a substitute for medium protein flour for the basic ingredients for making donuts. This study used a descriptive test to determine the nature and intensity of each sample by the author and a hedonic test to determine the level of preference of each sample given. Data collection through questionnaires and processed using SPSS version 25 and the type of test carried out was the One-Way ANOVA test. Based on the results for the taste aspect in the donut experiment with the substitution of jali seed flour, the results showed that wheat flour was preferred over jali seed flour, because jali seed flour had a bland taste. For the texture aspect in the donut experiment with the substitution of jali seed flour, the results showed that jali seed flour made the donut texture denser. From the taste aspect, the donut experiment with the substitution of jali seed flour showed that the donut was the most preferred by the panelists because the donut had the sweetest taste. In terms of texture, the donut experiment with barley flour substitution resulted in the donuts that the panelists preferred the most because they were the softest compared to the other treatments. Keywords: donuts, jail seed flour, taste texture